New genus and new species of spittlebugs (Hemiptera: Cercopidae) from the Philippines - Crispolon, Elorde Jr. S.; Guilbert, Eric; Yap, Sheryl A.; Soulier-Perkins, Adeline (European Journal of Taxonomy, 2021)
The following new taxa are described from the Philippines: Mioscarta nubisa Crispolon & Soulier-Perkins sp. nov., M. translucida Crispolon & Yap sp. nov. and Trigonoschema Crispolon & Soulier-Perkins gen. nov. with three new species: T. manoborum Crispolon & Soulier-Perkins sp. nov. (as type species), T. negrosensis Crispolon & Yap sp. nov and T. rubercella Crispolon &Guilbert sp. nov. Trigonoschema pallida (Lallemand, 1927) comb. nov. is transferred from Mioscarta Breddin, 1901. Descriptions of male genitalia are illustrated and keys to species of Philippine Mioscarta and Trigonoschema gen. nov. are provided. Although phylogenetic results confirm the monophyly of all genera and Trigonoschema being a distinct genus from Mioscarta, relationships between genera remain uncertain. A checklist of the genera and species of Cercopidae found in the Philippines is included.